2023
DOI: 10.4103/jos.jos_115_22
|View full text |Cite
|
Sign up to set email alerts
|

Oral hygiene awareness and practice in orthodontic patients in Makkah city: A cross sectional study

Abstract: OBJECTIVES: To evaluate the level of oral hygiene awareness and practice among orthodontic patients that have fixed appliances and investigate the differences in awareness as per age, gender, and education qualification. MATERIALS AND METHODS: A cross-sectional study with 250 patients was included. A questionnaire was used to collect information regarding the patient's oral hygiene. RESULTS: The level of awareness and oral hygiene practice wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…In alignment with our findings, Mahjoub et al found that orthodontic patients who obtained oral hygiene information had significantly better awareness levels about oral hygiene. [27] A noteworthy finding in this study is relation between the nature of the information received during orthodontic visits and the type of oral hygiene measures that the patients perceived as methods to prevent dental caries. Patients who reported receiving information about brushing methods, patients who received information about oral hygiene accessories, and those who received information about fluoridated mouthwash were significantly more likely to perceive performing appropriate oral hygiene as a manner to avoid dental caries.…”
Section: Discussionmentioning
confidence: 72%
“…In alignment with our findings, Mahjoub et al found that orthodontic patients who obtained oral hygiene information had significantly better awareness levels about oral hygiene. [27] A noteworthy finding in this study is relation between the nature of the information received during orthodontic visits and the type of oral hygiene measures that the patients perceived as methods to prevent dental caries. Patients who reported receiving information about brushing methods, patients who received information about oral hygiene accessories, and those who received information about fluoridated mouthwash were significantly more likely to perceive performing appropriate oral hygiene as a manner to avoid dental caries.…”
Section: Discussionmentioning
confidence: 72%
“…Despite the high prevalence of orthodontic treatment, there were notable gaps in oral hygiene knowledge and adherence among participants. This emphasizes the importance of comprehensive patient education initiatives to address these gaps and improve oral health outcomes in orthodontic patients [15]. Priyadarsi et al's study focused on assessing awareness about periodontal health among patients with fixed orthodontic appliances.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the influence of gender on satisfaction is vital for orthodontists in tailoring their approach to meet the unique needs and expectations of each patient, promoting greater patient comfort and ultimately better treatment outcomes. [ 23 24 ]…”
Section: Discussionmentioning
confidence: 99%